Cost is an important factor influencing active management of extremely preterm infants. (1st October 2018) - Ma, Li; Liu, Cuiqing; Cheah, Irene; Yeo, Kee Thai; Chambers, Georgina M.; Kamar, Azanna Ahmad; Travadi, Javeed; Oei, Ju Lee
Abstract: Aim: The attitudes of neonatologists towards the active management of extremely premature infants in a developing country like China are uncertain. Methods: A web‐based survey was sent to neonatologists from 16 provinces representing 59.6% (824.2 million) of the total population of China on October 2015 and December 2017. Results: A total of 117 and 219 responses were received in 2015 and 2017, respectively. Compared to 2015, respondents in 2017 were more likely to resuscitate infants <25 weeks of gestation (86% vs. 72%; p < 0.05), but few would resuscitate infants ≤23 weeks of gestation in either epoch (10% vs. 6%). In both epochs, parents were responsible for >50% of the costs of intensive care, but in 2017, significantly fewer clinicians would cease intensive care (75% vs. 88%; p < 0.05) and more would request for economic aid (40% vs. 20%; p < 0.05) if parents could not afford to pay. Resource availability (e.g. ventilators) was not an important factor in either initiation or continuation of intensive care (~60% in both epochs). Conclusion: Cost is an important factor in the initiation and continuation of neonatal intensive care in a developing country like China. Such factors need to be taken into consideration when interpreting outcome data from these regions.